Seconds away : a Mickey Bolitar novel - Coben, Harlan, 1962- (New York : G.P. Putnam's Sons, 2012)
"When tragedy strikes close to home, Mickey Bolitar and his new friends find themselves at the center of a murder mystery"--Provided by publisher.
Keywords: Murder -- Fiction; Adventure stories; High schools -- Fiction; Schools -- Fiction; Uncles -- Fiction; Detective and mystery stories; Young adult fiction; Mystery fiction